2004
DOI: 10.1016/s0014-5793(04)00031-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of altered regulation variants of dinitrogenase reductase‐activating glycohydrolase from Rhodospirillum rubrum

Abstract: In Rhodospirillum rubrum, nitrogenase activity is subject to posttranslational regulation through the adenosine diphosphate (ADP)-ribosylation of dinitrogenase reductase by dinitrogenase reductase ADP-ribosyltransferase (DRAT) and dinitrogenase reductase-activating glycohydrolase (DRAG). To study the posttranslational regulation of DRAG, its gene was mutagenized and colonies screened for altered DRAG regulation. Three di¡erent mutants were found and the DRAG variants displayed di¡erent biochemical properties i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 34 publications
(38 reference statements)
1
14
0
Order By: Relevance
“…DRAG activity, e.g., by affecting the association of DRAG with membranes (35). In accord with this observation, the corresponding region of ARH3 (␣-helix 5) is located on the protein surface, near to but outside of the proposed ADPR-binding region.…”
Section: Discussionsupporting
confidence: 56%
“…DRAG activity, e.g., by affecting the association of DRAG with membranes (35). In accord with this observation, the corresponding region of ARH3 (␣-helix 5) is located on the protein surface, near to but outside of the proposed ADPR-binding region.…”
Section: Discussionsupporting
confidence: 56%
“…In vivo studies showed that a R. rubrum DraG N100K variant lost regulation by ammonium, and this is predicted from our structure because the DraG K100 interaction with GlnJ R103 and the nearby R38 residues would be repulsive, thereby disfavoring complex formation (29,31). A case of two complementary changes is the interaction of A. brasilense DraG H112 with GlnZ D68 which become substituted by E112 and N68 respectively in R. rubrum permitting a similar side chain interaction.…”
Section: Comparison Of Glnz-drag Complex With the Putative Glnj-dragmentioning
confidence: 55%
“…Visual inspection of this structure suggested further functional and structural roles for certain amino acids ( Table 1). The functional relevance of Asp and other amino acids in and near the active site has also been demonstrated experimentally by inactivating mutations of dinitrogenase reductase-activating glycohydrolase in human or rat ADP-ribosylarginine hydrolase (29)(30)(31)(32). Interestingly, most functionally relevant Asp residues are not conserved in SelJ and J1-crystallin homologues or in six other bacterial proteins (Fig.…”
Section: Selj Experimental Validationmentioning
confidence: 87%
“…It has also been shown experimentally that dinitrogenase reductase ADP-ribosyltransferases require Mg-ATP and a free divalent metal for their activity. Furthermore, a binuclear Mn 2ϩ center, also found in arginases (33), has been detected in the active site of dinitrogenase reductase-activating glycohydrolases (31)(32)(33). Therefore, the modeled Mg 2ϩ ions may really point to the approximate positions of Mg 2ϩ or Mn 2ϩ in vivo.…”
Section: Selj Experimental Validationmentioning
confidence: 99%
See 1 more Smart Citation